Face verification : an introduction - Hameed, Shihab A.; Badurik, Waleed A. (IIUM Press, 2011)
Human biometrics especially face become widely used for different aspects of life. The face is the first defining characteristic that we use to identify people. It is recalled when trying to remember what someone looks like. We depend on it, for recognition. We carry photo IDs that we show as proofs of identity. On the cards are pictures of our face. Machine or automatic recognition of human faces has attracted a great deal of attention in the psychology, image processing, pattern recognition, neural science, computer security, and computer vision communities. It popularity results from its wide application ranging from static matching of controlled format photographs, such as passports, credit cards, driving licenses, and police photos, to real-time matching of video images for surveillance, access control, and security of public areas such as airports. Face is an essential application used in authentication. In this chapter, a brief background about automated face recognition is given then a short review about face recognition algorithms. Eigenface algorithm has been explained in details as one of the famous algorithms.